The Effectiveness of Nature-Based Learning on Early Childhood Gross Motor Development - Annuha, Adzkiah (JURNAL PENA PAUD, 2024)
This study aims to evaluate the effectiveness of nature-based learning in developing gross motor skills in early childhood. The research method used was an experiment with a pretest-posttest design involving two groups: an experimental group undergoing nature-based learning and a control group with conventional methods. The results showed that the experimental group experienced a significant increase in the mean score of gross motor skills from 19.70 to 26.20 (p < 0.05). In contrast, the control group only showed a small increase with an average change of 1.30 (p < 0.05). This finding indicates that nature-based learning is more effective than conventional methods in supporting early childhood gross motor skill development. The conclusions emphasize the importance of integrating nature-based learning in the early childhood education curriculum to support motor development and other developmental aspects. Further research is recommended to explore different nature-based learning approaches and their impact on holistic child development.